2019
DOI: 10.1016/j.ejca.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen variation is associated with adverse events of checkpoint inhibitors

Abstract: Background: Checkpoint inhibitors (CIs) are highly effective but can induce severe immune-related adverse events (irAEs), which cannot be predicted. We investigated whether human leukocyte antigen (HLA) genes predispose to developing of irAEs during therapy and thus hold a predictive role. Methods: We established a prospective observational single-centre study and collected data from patients with either metastatic nonesmall cell lung cancer (NSCLC) or metastatic melanoma, who were treated with antiePD-1 (prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 28 publications
1
85
0
Order By: Relevance
“…The Friends and QuIP initiatives for TMB harmonization recommended to include as much relevant genetic and molecular information as possible in these panels, to avoid the need to re-biopsy the patient for further information. In line with this recommendation, we propose to also include in gene panels for TMB quantification other potential immunotherapy biomarkers but also negative predictors of immunotherapy response [69,70] and variants predisposing to adverse reaction to immunotherapy [71,72]. These and other recommendations which emerge from the studies reviewed here, including the one from the TMB Harmonization Working Group, are summed up in Additional file 6: Table S6.…”
Section: Future Perspectives and Recommendationsmentioning
confidence: 89%
“…The Friends and QuIP initiatives for TMB harmonization recommended to include as much relevant genetic and molecular information as possible in these panels, to avoid the need to re-biopsy the patient for further information. In line with this recommendation, we propose to also include in gene panels for TMB quantification other potential immunotherapy biomarkers but also negative predictors of immunotherapy response [69,70] and variants predisposing to adverse reaction to immunotherapy [71,72]. These and other recommendations which emerge from the studies reviewed here, including the one from the TMB Harmonization Working Group, are summed up in Additional file 6: Table S6.…”
Section: Future Perspectives and Recommendationsmentioning
confidence: 89%
“…A previous report evaluating the relationship between irAEs and HLA types showed that pruritus and colitis were associated with HLA-DRB1 * 11 : 01 and HLA-DQB1 * 03 : 01, respectively [40]. However, the association between hepatic irAEs and HLA types has not been demonstrated yet.…”
Section: Hla Types and Hepatic Iraementioning
confidence: 94%
“…They are significantly associated with a large number of autoimmune diseases and may also be associated with irAEs. There is evidence that specific individual HLA types were enriched in colitis , pruritis , rheumatoid arthritis and hypophysitis . In conventional T1DM, the highest risk derives from the heterozygous combination of DR3‐DQ2 and DR4‐DQ8 with increased risk still conferred by each of these alleles on their own .…”
Section: Genetic Predispositionmentioning
confidence: 99%